Conhecimento sobre hipertensão arterial sistêmica e sua farmacoterapia em portadores usuários da farmácia básica do município de São Francisco de Paula, RS - Motter, Fabiane Raquel (Universidade do Vale do Rio dos Sinos, 2011)
High blood pressure (HBP) is a multifactorial condition and important risk factor for developing cardiovascular disease. However, about 30% of patients with HPB do not have controlled blood pressure levels. Patient’s knowledge about hypertension and its pharmacotherapy has been described as important factor to control this condition. The aim of this study was to evaluate knowledge about hypertension and its treatment in users of antihypertensives agents. A cross-sectional study was performed, with adults 20 years or older, that obtained antihypertensives agents at Public Pharmacy in São Francisco de Paula/RS. The fieldwork was realized between tNovember/2010 and February/2011. A standardized questionnaire was used to collected on knowledge of hypertension (risk factors, thresholds for blood pressure levels, complications and non-pharmacological treatment) and its pharmacological treatment (name, indication, dose, frequency / schedule of administration and duration of treatment). This knowledge about pharmacological treatment was measured through a score (0-5) and related factors. It was interviewed 678 users. The mean knowledge score was 3.27 (SD = 1.16). Lower age, higher schooling, white skin people, better selfreported health and lower prescription drugs were associated with a higher knowledge scores. Finally, knowledge is still limited about all aspects measured. This result can compromise the use correct and safe of drugs. It’s suggesting that hypertensive’s patient need for better counseling and care to high blood pressure control.
Keywords: Conhecimentos; Atitudes e prática em saúde; Hipertensão; Farmacoterapia; Anti-hipertensivos; Health knowledge; Attitudes; Practice; Hypertension; Drug therapy; Antihypertensive agents; ACCNPQ::Ciências da Saúde::Saúde Coletiva